Is There an Association Between Fixed Orthodontic Treatment and Initiation of Eating Disorders? A Review of Currently Available Evidence - Koukou, Melina; Javed, Fawad; Michelogiannakis, Dimitrios (Frontiers in Oral Health, 2021)
Objectives: The aim was to review the available literature regarding the potential association between fixed orthodontic treatment (OT) and the onset of eating disorders (EDs). Method and Materials: Six indexed databases were searched until November 2020. The inclusion criteria were as follows: (a) patients undergoing fixed OT and (b) EDs in relation to fixed OT. Commentaries, letters to the Editor, reviews, and studies in patients with EDs not undergoing fixed OT were excluded. The pattern of the present review was customized to summarize the pertinent information. Results: Four out of 10,076 initially-identified studies were included, and all of them were case reports. All patients were females, and the EDs reported were either anorexia nervosa (AN) or bulimia nervosa (BN). In three case reports, patients developed EDs after the initiation of OT. Fixed OT was performed in all the studies, and a variety of oral complications such as sore mouth, gingivitis, tooth surface demineralization, and others were reported. Conclusion: Based upon the limited available evidence, the association between OT and the onset of EDs remains unclear. Further well-designed observational clinical studies are needed in this regard.